The Role of Tissue Inhibitors of Metalloproteinases in Organ Development and Regulation of ADAMTS Family Metalloproteinases in Caenorhabditis elegans. Issue 2 (16th April 2019) - Kubota, Yukihiko; Nishiwaki, Kiyoji; Ito, Masahiro; Sugimoto, Asako
Abstract: Remodeling of the extracellular matrix supports tissue and organ development, by regulating cellular morphology and tissue integrity. However, proper extracellular matrix remodeling requires spatiotemporal regulation of extracellular metalloproteinase activity. Members of the ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) family, including MIG-17 and GON-1, are evolutionarily conserved, secreted, zinc-requiring metalloproteinases. Although these proteases are required for extracellular matrix remodeling during gonadogenesis in Caenorhabditis elegans, their in vivo regulatory mechanisms remain to be delineated. Therefore, we focused on the C. elegans tissue inhibitors of metalloproteinases (TIMPs), TIMP-1 and CRI-2 . Analysis of the transcription and translation products for GFP/Venus fusions, with TIMP-1 or CRI-2, indicated that these inhibitors were secreted and localized to the basement membrane of gonads and the plasma membrane of germ cells. A timp-1 deletion mutant exhibited gonadal growth defects and sterility, and the phenotypes of this mutant were fully rescued by a TIMP-1::Venus construct, but not by a TIMP-1 (C21S)::Venus mutant construct, in which the inhibitor coding sequence had been mutated. Moreover, genetic data suggested that TIMP-1 negatively regulates proteolysis of the α1 chain of type IV collagen. We also found that the loss-of-function observed for the mutants timp-1 and cri-2 involves a partial suppression of gonadal defects found for the mutants mig-17 /ADAMTS and gon-1 /ADAMTS, and that this suppression was canceled upon overexpression of gon-1 or mig-17, respectively. Based on these results, we propose that both TIMP-1 and CRI-2 act as inhibitors of MIG-17 and GON-1 ADAMTSs to regulate gonad development in a noncell-autonomous manner.